Spatially resolved spectroscopy across stellar surfaces: V. observational prospects: toward Earth-like exoplanet detection - Dravins, Dainis; Ludwig, Hans-Günter; Freytag, Bernd (Astronomy and astrophysics, 2021)
Context. High-precision stellar analyses require hydrodynamic 3D modeling. Testing such models is feasible by retrieving spectral line shapes across stellar disks, using differential spectroscopy during exoplanet transits. Observations were presented in Papers I, II, and III, while Paper IV explored synthetic data at hyper-high spectral resolution for different classes of stars, identifying characteristic patterns for Fe I and Fe II lines. Aims. Anticipating future observations, the observability of patterns among photospheric lines of different strength, excitation potential and ionization level are examined from synthetic spectra, as observed at ordinary spectral resolutions and at different levels of noise. Time variability in 3D atmospheres induces changes in spectral-line parameters, some of which are correlated. An adequate calibration could identify proxies for the jitter in apparent radial velocity to enable adjustments to actual stellar radial motion. Methods. We used spectral-line patterns identified in synthetic spectra at hyper-high resolution in Paper IV from 3D models spanning T-eff = 3964-6726K (spectral types similar to K8V-F3V) to simulate practically observable signals at different stellar disk positions at various lower spectral resolutions, down to lambda/Delta lambda = 75 000. We also examined the center-to-limb temporal variability. Results. Recovery of spatially resolved line profiles with fitted widths and depths is shown for various noise levels, with gradual degradation at successively lower spectral resolutions. Signals during exoplanet transit are simulated. In addition to Rossiter-McLaughlin type signatures in apparent radial velocity, analogous effects are shown for line depths and widths. In a solar model, temporal variability in line profiles and apparent radial velocity shows correlations between jittering in apparent radial velocity and fluctuations in line depth. Conclusions. Spatially resolved spectroscopy using exoplanet transits is feasible for main-sequence stars. Overall line parameters of width, depth and wavelength position can be retrieved already with moderate efforts, but a very good signal-to-noise ratio is required to reveal the more subtle signatures between subgroups of spectral lines, where finer details of atmospheric structure are encoded. Fluctuations in line depth correlate with those in wavelength, and because both can be measured from the ground, searches for low-mass exoplanets should explore these to adjust apparent radial velocities to actual stellar motion.